Family, slavery, and love in the early American republic : the essays of Jan Ellen Lewis - Lewis, Jan, 1949-2018 (Published by the Omohundro Institute of Early American History and Culture and the University of North Carolina Press Ser., 2021)
One of the finest historians of her generation, Jan Ellen Lewis transformed our understanding of the early US Republic. Her groundbreaking essays defined the emerging fields of gender and emotions history. This book collects thirteen of Lewis's most important essays.